Irenaeus’s engagement with rhetorical theory in his Exegesis of the Johannine Prologue in Adversus Haereses 1.8.5-1.9.3 - Harris, B (Brill Academic Publishers, 2018)
While scholars have long recognised Irenaeus’s acquaintance with rhetorical theory, the role of rhetorical theory in Irenaeus’s scriptural exegesis has only recently come to light. In the last few years, Lewis Ayres (2015) and Anthony Briggman (2015, 2016) have argued for the central importance of Greco-Roman literary and rhetorical theory to Irenaeus’s approach to scripture. This paper will build on the work of Ayres and Briggman by exploring Irenaeus’s engagement with rhetorical theory in his interpretation of the Johannine prologue in AH 1.8.5-9.3. In this paper, I will argue that Irenaeus’s exegetical strategy in AH 1.8.4-9.3 is best understood in light of the question of authorial intent as formulated in rhetorical handbooks. Specifically, I will argue that Irenaeus presents his argument as a defence of the scriptum of the prologue, and so follows the conventions laid out in rhetorical handbooks for a dispute between scriptum et voluntas.